Introns increase gene expression in Caenorhabditis elegans by a mechanism that must be at least partly different than in plants - Alan B. Rose; Aaron Baer; Isaac Shaker; J. Grey Monroe; Ian Korf; Lesilee S. Rose (Scientific Reports)
Abstract The wide diversity of organisms in which introns stimulate gene expression suggests that this is an ancient phenomenon. However, the mechanisms through which introns boost expression remain poorly understood, and the degree the which the action of introns is evolutionarily conserved is unknown. Here we compared the effect on expression of introns at different positions and tested ten different introns at the same location in a reporter gene in single-copy transgenic nematodes. The introns boosted expression most when near the start of the gene, as previously observed in several organisms. All ten introns tested at the same position increased mRNA accumulation 10- to 17-fold, in contrast to plants where introns vary widely in their effect on expression and relatively few increase mRNA levels 10-fold or more. These results suggest that some aspects of the mechanisms through which introns boost expression are fundamentally different in nematodes and plants.